Deficiency of peptidoglycan and lipopolysaccharide components in Rickettsia tsutsugamushi. - Amano, K (1987)
Analyses of chemical composition in whole cells of Rickettsia tsutsugamushi were performed and compared with those of the other rickettsiae and gram-negative bacteria. The results indicated that R. tsutsugamushi does not contain detectable amounts of 3-deoxy-D-mannooctulosonic acid, heptose, muramic acid, or glucosamine (less than 2, less than 2, less than 3, and less than 3 nmol/mg, respectively). The microorganism was found to contain four kinds of fatty acids (16:0, 18:0, 18:1, and 18:2), but not hydroxy fatty acids. Furthermore, in analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by silver or Coomassie blue staining, lipopolysaccharide bands were not detected in preparations treated with proteinase K. It is concluded that R. tsutsugamushi has little or no peptidoglycan or lipopolysaccharide.